Encouraging human-wildlife coexistence in Scotland: implementing key stakeholder perspectives and international mechanisms to design a wildlife coexistence fund - Navarrete Zur, Olivia (The University of Edinburgh, 2025)
Biodiversity worldwide is facing an accelerating crisis, driven by agricultural intensification, unsustainable land management practices, habitat loss, and the escalating impacts of climate change. This decline not only endangers wild species but also vital ecosystem services that support human livelihoods, such as clean water, pollination, and food production. As nature restoration efforts and species reintroductions increase, constructive human-wildlife coexistence (HWC) becomes an urgent concern for policy and practice. Agricultural and rural communities around the world often bear a disproportionate share of the costs and challenges associated with sharing land with wildlife. In Scotland, despite commitments to tackle the biodiversity and climate crises, current government schemes continue to support intensive agricultural production and lack the ambition and scope to adequately support HWC or nature recovery at the scale and pace required. This thesis explores strategies to support HWC in Scotland, addressing the urgent need for financial mechanisms that effectively encourage, recognize, and reward efforts by key Scottish stakeholders, including farmers, crofters, land managers, and rewilding practitioners, to coexist with wildlife. It investigates the feasibility of a Scottish Wildlife Coexistence Fund (WCF), drawing on international examples of government-backed outcome-based funding for HWC and semi-structured interviews with key Scottish stakeholders regarding their main concerns and motivations for a potential WCF. The analysis of international funding schemes identified six recurrent characteristics for successful HWC: (1) robust stakeholder involvement, (2) clear and measurable outcomes, (3) diversified financial mechanisms, (4) comprehensive education and awareness initiatives, (5) conditional payment structures, and (6) adaptive flexibility. Scottish stakeholders, including farmers, crofters, land managers, and rewilding practitioners, voiced significant concerns, such as entrenched conflicts over land-use values, rigid and ill-fitting scheme requirements, insufficient government action and public investment, and high administrative burdens. Despite these challenges, strong motivations for reform emerged, with participants advocating for greater bottom-up engagement, improved public education, recognition of existing coexistence efforts, and the adaptation of successful international models. The findings underscore a persistent gap between Scotland's ambitious biodiversity goals and the practical realities faced by key stakeholders. This study concludes that a dedicated Wildlife Coexistence Fund, incorporating the identified principles of effective funding models and addressing stakeholder concerns, is crucial. Such a fund would serve as a vital instrument for achieving Scotland's biodiversity and climate ambitions through inclusive and adaptive land stewardship, fostering trust and bridging the policy-practice divide by empowering rural communities as active stewards for nature recovery.
Keywords: Human–Wildlife Coexistence; Policy; Outcome-Based Funding; Agricultural Policy; Crofting; Farming; Land Management; Rewilding; Biodiversity; Stakeholder Engagement